Educação ambiental dialógico-crítica e sua relação com a prática da agroecologia e da educação do campo no território do extremo sul da Bahia: entre o descompasso e o desafio de transformação - Ferreira, Caroline Lins Ribeiro (2018)
This thesis highlights experiences related to the practices of rural education and agroecology, formative matrices and practices that can help in the problematization of socio-environmental issues traditionally debated by environmental education, adopting a dialogical-critical perspective, with a view to the formation of sustainable societies . The qualitative methodology, with approximations of the dialectical historical materialist method, made it possible to show contradictions in the agrarian context of the extreme south of Bahia and also to identify peasant practices promoted by the Landless Rural Workers Movement, which have identified articulations and possible paths for the overcoming antagonistic contradictions, faced with the degrading historical moment, marked by the absence of agrarian reform and other obstacles in the formation of sustainable societies to overcome these antagonistic contradictions. We make observations, individual and collective interviews with subjects of this territory and systematize the information in field diary from the categories of environmental education, field education and agroecology. During the field research Ne, after the analysis of all the systematized material, the research was based on the experiences of the School of Agroecology and Agroforestry Egídio Brunetto, its articulations with rural schools, as well as the classes with the adult literacy method "Yes I Can". In all experiments there is a clear intention to build systematic processes of agroecological and field education, based on the agrobiodiverse productive matrix and the pedagogical matrix of the Landless Workers' Movement, which associate collective organization, work, culture, social struggle and history, in their educational actions at school and beyond. As a result, we have verified that these experiences, with all the contradictions that surround them, have the potential to problematize socio-environmental issues traditionally debated in the area of environmental education, particularly in a dialogic-critical perspective, which involves denouncing the agribusiness productive model its anti-ecological and socially unequal pedagogy) and the announcement of a praxis that tries to tune the limits and the ecosystemic possibilities with the productive and cultural needs of the peasants, implying a new work culture and new socio-environmental relations in the direction of to form sustainable societies. The research identifies the principles and practices of Social Movements in the field and discusses how they can articulate a dialogic-critical approach to socio-environmental issues, while also indicating the potential of this approach to environmental education for the strengthening of socio-environmental practices related to rural education and agroecology.